Facility-level integration of hypertension and diabetes services with HIV treatment in sub-Saharan Africa: Observational evidence from Malawi, South Africa, and Zambia - Linda Sande; Mariet Benade; Timothy Tchereni; Aniset Kamanga; Vinolia Ntjikelane; Allison Morgan; Taurai Makwalu; Wyness Phiri; Priscilla Lumano-Mulenga; Prudence Haimbe; Hilda Shakwelele; Amy Huber; et al. (PLoS ONE, 2026)
Background A growing number of people living with HIV (PLHIV) also have non-communicable diseases (NCDs). Shifting to an integrated delivery model may facilitate care-seeking and improve outcomes for people with a dual burden of HIV and NCDs. We describe the current state of integration of hypertension and diabetes care into HIV treatment in Malawi, South Africa and Zambia. Methods We administered structured interviews to HIV treatment providers in 41 primary healthcare facilities to evaluate how NCD care is provided to PLHIV accessing antiretroviral therapy (ART). We defined integration as provision of NCD services within the HIV clinic. The potential degree of integration in HIV clinics ranged from not integrated at all (no NCD services) to fully integrated (all NCD services). We also surveyed a sample of ART clients about their access to integrated care. Results The degree of integration varied across the facilities and countries. All facilities in South Africa reported being fully integrated for HIV care and hypertension and diabetes, and most providers in South Africa identified no barriers to integration. Integration was much less complete in Malawi and Zambia, with most facilities offering hypertension and diabetes screening/diagnosis and support but limited treatment or disease monitoring services. Frequently cited barriers to integration in Malawi and Zambia were limited staff knowledge of integrated care provision and facility space constraints. ART clients’ experience with integrated services mirrored provider responses. Over 90% of survey participants in South Africa reported HIV and non-HIV visit and medication collection alignment, compared to less than half in Malawi and Zambia. Conclusions The level of integration of hypertension and diabetes care with HIV treatment varies widely across facilities in Malawi, South Africa, and Zambia, despite each country having national guidelines that promote integration. Interventions to increase integration must consider differences among facilities at baseline.